Application of The Ethno-STEM Based Discovery Learning Model to Improve Students Science Literacy - Beni Setiawan; Viona Alvinia Nabila; Muhammad Romadhoni (Universitas Syiah Kuala, 2025)
Science literacy among students is fundamental to the development of the competencies and qualities needed in the 21st century. Therefore, teachers play an important role in helping students improve these skills through appropriate learning strategies. This study aims to describe students' science literacy integrated with Ethno-STEM, where the ethnoscience introduced is Sidoarjo's signature shrimp paste, using a pre-experimental design in a one-group pretest-posttest design. The research sample consisted of 31 ninth-grade students from class IX-B at one of Sidoarjo's public junior high schools. The instruments used were pretest and posttest sheets. Data collection techniques were conducted through tests, while data analysis techniques involved paired t-tests and N-Gain analysis. The t-test results showed a significant difference in the average science literacy scores before and after the implementation of the Etno-STEM-based Discovery Learning model. Additionally, the N-Gain analysis yielded a value of 0.8, which falls into the high category. Based on these findings, it can be concluded that the implementation of the discovery learning model based on Etno-STEM in science education on biotechnology is effective in improving students' science literacy